Value Investment Strategies and Asset Pricing: A Case of Pakistan Stock Exchange (PSX) - Anjali bai; Imran Umer Chhapra (JISR Management and Social Sciences & Economics, 2021)
The Capital Asset Pricing Model (CAPM) measures only a linear relationship between the Risk and the Return. However, market dynamics and anomalies calls for understanding the relationship in between risk and return from non-linear perspective. Thus, current study explores an opportunity to study asset value anomalies by Constructing Decile Portfolio for the period starting from 2001 to 2018 with 900 firms listed. GMM (Generalized method of moment  and Wald test are applied to see the robustness of results. For further analysis, Risk Adjusted CAPM, Fama French 3 Factor (FF3) and 5 Factor (FF5) are applied. Empirical results indicate that value effect and debt to equity ratio are essential factors and genuinely explain what CAPM fails to explain. The findings from the study recommend that investing in High value and high leverage firm will generate abnormal returns to investors. Taking long position in high value firm and short position in low value firms and same with debt to equity anomaly. The results will help financial analyst develop investment strategies for well diversified and efficient portfolios. These results can also be helpful to financial firm and security analyst in the financial market where they can take appropriate capital budget decisions while investing.